Details of the southern aisles in the Bhandasar Temple - Temples of India Project Team (Jio Institute, 2024)
Details of the southern aisles in the Bhandasar Temple, which separates the exterior walls of the mandapa (pillared hall) and the central dome of the temple. The windows/doorway puncture the exterior wall equidistantly. Wooden planks used as doorways are beautified with frames of paintings. The paintings are from various themes like the depiction of twenty Tirthankaras, the work of Jain monks, important places of pilgrimage, and teachings of the Jain traditions, among several others.